Fractional Dynamics in Mechanical Manipulation - Lima, Miguel F. M. (2008)
This paper analyzes the signals captured during the movement of a mechanical manipulator carrying a liquid container. In order to study the signals, an experimental setup is implemented. The system acquires data from the sensors, in real time, and, in a second phase, processes them through an analysis package. The analysis package runs offline and handles the recorded data. The results show that the Fourier spectrum of several signals presents a fractional behavior. The experimental study provides useful information that can assist in the design of a control system to be used in reducing or eliminating the effect of vibrations.